Low cost micro-nanoimprinted light trapping glass for photovoltaic cells

CN122952697APending Publication Date: 2026-10-20XINJIANG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610819755.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]本发明的目的在于克服现有的陷光结构无法精准、可控制备和制备成本昂贵的问题,提供了一种用于光伏电池的低成本微纳压印陷光玻璃

Benefits of technology

[0020]本发明提出一种用于光伏电池的低成本微纳压印陷光玻璃,该陷光玻璃表面具有精准、可控的微纳陷光结构,所述微纳陷光结构由UV-LIGA制备的压印模板经紫外纳米压印转移形成。与精准制备陷光结构的电子束刻蚀技术相比,可以大大降低制备成本,且可以大面积制备;与湿法刻蚀技术相比,该方法能精准,可控制备陷光结构。此外,电池表面具有陷光结构,能够提升电池组件的自清洁能力,对改善组件的可持续性具有重要的应用价值。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a low-cost micro / nano imprinted light-trapping glass for photovoltaic cells, belonging to the fields of micro / nano light-trapping technology and solar cell devices. The light-trapping glass surface possesses a precise and controllable micro / nano light-trapping structure, which can be fabricated using a combination of UV-LIGA and ultraviolet nanoimprinting techniques, featuring low fabrication cost and large-area fabrication capabilities. Designing the micro / nano photonic structure on the surface of the solar cell device effectively reduces reflection loss and extends the photon travel path and residence time in the response layer, enabling the cell to achieve high photoelectric conversion efficiency with a thinner response layer. Furthermore, through light manipulation, the thickness of the absorption layer can be reduced while enhancing light absorption, thereby lowering production costs by using less material. Solar cells based on the light-trapping structure can improve the self-cleaning capability of the cell module, which has significant application value for improving the sustainability of the module.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of micro-nano light trapping technology and solar cell devices, specifically to a low-cost micro-nano imprinted light trapping glass for photovoltaic cells. Background Technology

[0002] Improving the photoelectric conversion efficiency of solar cells and reducing production costs have always been goals pursued by the photovoltaic industry. These two are typically mutually exclusive; high conversion rates often come at the cost of high costs. Light manipulation based on micro / nano light-trapping structures can effectively broaden the solar cell's response spectrum, increase the number of photons in the absorption layer, and extend the optical path and residence time, thereby improving the device's photoelectric conversion efficiency. Through light manipulation, it is possible to enhance light absorption while reducing the thickness of the absorption layer, thus lowering production costs by using less material.

[0003] In recent years, various light-trapping structures for solar cells have been designed, mainly including surface plasmon resonances, photonic crystals, diffraction gratings, and optical resonators. These light-trapping strategies primarily utilize techniques such as electron beam etching, ultraviolet nanoimprinting, or wet etching, which have certain limitations. Electron beam etching can precisely fabricate light-trapping structures, but its high cost prevents large-scale application. Wet etching can reduce the fabrication cost of surface light-trapping structures, but it cannot precisely fabricate them. Therefore, developing methods for precisely and controllably fabricating light-trapping structures on the surface of solar cell glass has significant application value and scientific importance for accelerating its industrialization. Summary of the Invention

[0004] The purpose of this invention is to overcome the problems of existing light-trapping structures being unable to be precisely and controllably prepared and having high manufacturing costs, and to provide a low-cost micro / nano imprinted light-trapping glass for photovoltaic cells.

[0005] A low-cost micro / nano imprinted light-trapping glass for photovoltaic cells includes a glass substrate and a micro / nano light-trapping structure formed on the surface of the glass substrate. Solar cells based on the light-trapping structure can effectively manipulate photons, broaden the solar cell's response spectrum, increase the number of photons in the absorption layer, and extend the optical path and residence time, thereby improving the device's photoelectric conversion efficiency. Through light manipulation, the thickness of the absorption layer can be reduced while enhancing light absorption, thus lowering production costs by using less material. Furthermore, solar cells based on the light-trapping structure possess self-cleaning capabilities, which can significantly improve the device's sustainability and photoelectric performance.

[0006] The method for preparing low-cost micro / nano imprinted light-trapping glass for photovoltaic cells includes the following steps.

[0007] Step 1: Prepare the imprint template using UV-LIGA.

[0008] Step 1: Substrate cleaning: Select a suitable substrate for standard semiconductor cleaning processes;

[0009] Step 2: Spin-coating photoresist: Select the appropriate photoresist based on the height of the light-trapping structure for spin-coating;

[0010] Step 3: Fabricate the photomask: Fabricate the photomask according to the bottom diameter and period of the light trapping structure;

[0011] Step 4: Pattern Transfer: The pattern on the photomask is transferred to the photoresist through exposure and development;

[0012] Step 5: Thermal reflow process: Thermal reflow can keep the structure in the photoresist in a semi-molten state, and structures such as cones, frustums and hemispheres can be prepared by diffusion through surface tension;

[0013] Step 6: Template preparation: A nickel template is prepared using an electroforming process.

[0014] Step 2: Use ultraviolet nanoimprinting technology to imprint the template onto the surface of the solar cell or glass.

[0015] Step 1: Spin-coating the photoresist: Select a suitable photoresist and spin-coat it onto the surface of the solar cell or glass;

[0016] Step 2: Pattern Transfer: The template structure is transferred once or twice through molding and exposure.

[0017] Step 3: Demolding: Separate the embossing template and the embossing adhesive to obtain the embossed structure.

[0018] In the process of precisely and controllably preparing the light-trapping structure on the surface of solar cell glass, practical and effective relevant process parameters are used, such as: the type and thickness of photoresist and imprinting adhesive, the rotation speed of the spin coater, the shape, diameter, period and arrangement of the mask, and the temperature and time of the thermal reflow process.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] This invention proposes a low-cost micro / nano imprinted light-trapping glass for photovoltaic cells. The surface of this light-trapping glass possesses a precise and controllable micro / nano light-trapping structure, formed by ultraviolet nanoimprint transfer from an imprinting template prepared by UV-LIGA. Compared to electron beam etching technology for precisely preparing the light-trapping structure, this method significantly reduces fabrication costs and allows for large-area fabrication. Compared to wet etching technology, this method offers precise and controllable light-trapping structure preparation. Furthermore, the light-trapping structure on the cell surface enhances the self-cleaning capability of the cell module, which has significant application value for improving the sustainability of the module. Attached Figure Description

[0021] Figure 1 SEM image of a cylindrical structure (period 20µm);

[0022] Figure 2 SEM image of a hemispherical structure (period 20µm);

[0023] Figure 3 SEM image of the hemispherical pit structure (period 20µm);

[0024] Figure 4 SEM image of a hemispherical structure (period 12µm);

[0025] Figure 5 SEM image of the hemispherical pit structure (period 12µm);

[0026] Figure 6 A static diagram of a water droplet in a planar glass structure;

[0027] Figure 7 A static image of a water droplet in a hemispherical (20µm period) glass structure.

[0028] Figure 8 A static image of a water droplet in a hemispherical concave (period 20µm) glass structure.

[0029] Figure 9 A static image of a water droplet in a hemispherical (12µm period) glass structure;

[0030] Figure 10 A static image of a water droplet in a hemispherical concave (period 12µm) glass structure.

[0031] Figure 11 Transmission spectra of hemispherical and hemispherical pitted glass with different periods;

[0032] Figure 12 The graph shows the photoelectric conversion efficiency of crystalline silicon solar cells based on hemispherical and hemispherical pit structures with different periods. Detailed Implementation

[0033] The technical solutions in the embodiments of the present invention will be further described in detail below with reference to the accompanying drawings. The described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without making innovative improvements are all within the protection scope of the present invention.

[0034] Example 1 1. Prepare the photolithography template. In this embodiment, the template is a chromium template with a period of 20µm and a circular hole diameter of 10µm. 2. Substrate Cleaning: Quartz glass was used as the substrate in this experiment. To remove impurities and oil stains from the substrate surface, it needed to be cleaned before preparation. The substrate was ultrasonically cleaned for 10 minutes in acetone solution, ethanol solution, and deionized water, respectively, and then dried with a nitrogen gun. To remove moisture from the substrate surface and increase its adhesion, the dried substrate was heat-treated at 120 ℃ for 30 minutes. 3. Spin Coating: The choice of photoresist plays a crucial role in the success of the experiment. In this experiment, commercially available positive photoresist AZ6130 (model AZ6130, Anzhi, positive photoresist) was used for spin coating. A layer of photoresist was spin-coated onto the substrate surface using a spin coater at a low speed of 500 r / min for 5 s and a high speed of 1000 r / min for 30 s. 4. Pre-baking: After spin coating of the photoresist, the substrate needs to be pre-baked to remove excess water and solvent and to cure the photoresist. The pre-baking operation is performed using a heating platform at 100 ℃ for 3 minutes. 5. Exposure and Development: The exposure step is one of the key steps in pattern preparation. Contact exposure is performed on the mask according to the desired pattern, with an exposure energy of 60 mJ / cm². After exposure, the substrate is developed to obtain the photoresist pattern. A 5% NaOH solution is used as the developer, and the development time is 30 seconds. 6. Electroforming master copy: Before electroplating, a 100 nm thick layer of nickel is deposited on the substrate as a seed layer for electroplating. Then, the photoresist template is immersed in a salt solution containing nickel metal for electroplating. After electroplating, the template is demolded to prepare the nickel template. 7. Spin-coating embossing adhesive: A layer of UV imprint photoresist (Huahai Chengke 3604-09) was spin-coated onto a quartz glass substrate using a spin coater. Spin-coating steps: The imprint photoresist was dropped onto the glass surface and rotated at a low speed of 300 r / min for 5 seconds, then at a high speed of 1000 r / min for 15 seconds. 8. Lamination and exposure: The template is pressed onto a glass substrate coated with photoresist and placed inside a UV nanoimprinter. Heating and pressurizing are applied to completely fill the voids in the nickel nanoimprint template with the imprinting resin. Then, the imprinting resin is cured by UV exposure at an energy of 20 mJ / cm² for 10 min. 9. Demolding: Finally, the embossing template and embossing adhesive are separated to obtain the embossed structure. The light-trapping structure prepared in this embodiment is a cylindrical structure with a period of 20 μm, a base diameter of 10 μm, and a height of 10 μm. Its morphological characteristics are shown in the attached figure. Figure 1 As shown.

[0035] Example 2 1. Prepare the photolithography template. In this embodiment, the template is a chromium template with a period of 20µm and a circular hole diameter of 10µm. 2. Substrate Cleaning: Quartz glass was used as the substrate in this experiment. To remove impurities and oil stains from the substrate surface, it needed to be cleaned before preparation. The substrate was ultrasonically cleaned for 10 minutes in acetone solution, ethanol solution, and deionized water, respectively, and then dried with a nitrogen gun. To remove moisture from the substrate surface and increase its adhesion, the dried substrate was heat-treated at 120 ℃ for 30 minutes. 3. Spin Coating: The choice of photoresist plays a crucial role in the success of the experiment. In this experiment, commercially available positive photoresist EPG590 (model: EPG590, Yongguang Group, positive photoresist) was used for spin coating. A layer of photoresist was spin-coated onto the substrate surface using a spin coater at a low speed of 500 r / min for 5 s and a high speed of 1000 r / min for 30 s. 4. Pre-baking: After spin coating of the photoresist, the substrate needs to be pre-baked to remove excess water and solvent and to cure the photoresist. The pre-baking operation is performed using a heating platform at 100 ℃ for 3 minutes. 5. Exposure and Development: The exposure step is one of the key steps in pattern preparation. Contact exposure is performed on the mask according to the desired pattern, with an exposure energy of 60 mJ / cm². After exposure, the substrate is developed to obtain the photoresist pattern. A 5% NaOH solution is used as the developer, and the development time is 30 seconds. 6. Hot Reflow Process: The hot reflow process involves treating a cylindrical structure at high temperature, bringing it to a semi-molten state. Due to surface tension, the cylindrical microstructure gradually diffuses into a hemispherical structure. This process also improves the surface roughness of the microstructure, achieving optical-grade performance. This method requires precise temperature and time control. In this experiment, the reflow temperature was 150 ℃ and the time was 3 min. 7. Electroforming master copy: Before electroplating, a 100 nm thick layer of nickel is deposited on the substrate as a seed layer for electroplating. Then, the photoresist template is immersed in a salt solution containing nickel metal for electroplating. After electroplating, the template is demolded to prepare the nickel template. 8. Spin-coating embossing adhesive: A layer of UV imprint photoresist (Huahai Chengke 3604-09) was spin-coated onto a quartz glass substrate using a spin coater. Spin-coating steps: The imprint photoresist was dropped onto the glass surface and rotated at a low speed of 300 r / min for 5 seconds, then at a high speed of 1000 r / min for 15 seconds. 9. Lamination and exposure: The template is pressed onto a glass substrate coated with photoresist and placed inside a UV nanoimprinter. Heating and pressurizing are applied to completely fill the voids in the nickel nanoimprint template with the imprinting resin. Then, the imprinting resin is cured by UV exposure at an energy of 20 mJ / cm² for 10 min. 10. Demolding: Finally, the embossing template and embossing adhesive are separated to obtain the embossed structure. The light-trapping structure prepared in this embodiment is a hemispherical structure with a period of 20 μm, a base diameter of 10 μm, and a height of 5 μm, as shown in the attached figure. Figure 2 As shown.

[0036] Example 3 Using the template prepared in Example 2, a secondary imprinting technique using ultraviolet nanoimprinting can be performed to obtain a light-trapping structure opposite to the template. The secondary light-trapping structure is a hemispherical pit structure with a period of 20 μm, a base diameter of 10 μm, and a height of 5 μm. Its morphological characteristics are shown in the attached figure. Figure 3 As shown.

[0037] Example 4 1. Prepare the photolithography template. In this embodiment, the template is a chromium template with a period of 12µm and a circular hole diameter of 10µm. 2. Substrate Cleaning: Quartz glass was used as the substrate in this experiment. To remove impurities and oil stains from the substrate surface, it needed to be cleaned before preparation. The substrate was ultrasonically cleaned for 10 minutes in acetone solution, ethanol solution, and deionized water, respectively, and then dried with a nitrogen gun. To remove moisture from the substrate surface and increase its adhesion, the dried substrate was heat-treated at 120 ℃ for 30 minutes. 3. Spin Coating: The choice of photoresist plays a crucial role in the success of the experiment. In this experiment, commercially available positive photoresist EPG590 (model: EPG590, Yongguang Group, positive photoresist) was used for spin coating. A layer of photoresist was spin-coated onto the substrate surface using a spin coater at a low speed of 500 r / min for 5 s and a high speed of 1000 r / min for 30 s. 4. Pre-baking: After spin coating of the photoresist, the substrate needs to be pre-baked to remove excess water and solvent and to cure the photoresist. The pre-baking operation is performed using a heating platform at 100 ℃ for 3 minutes. 5. Exposure and Development: The exposure step is one of the key steps in pattern preparation. Contact exposure is performed on the mask according to the desired pattern, with an exposure energy of 60 mJ / cm². After exposure, the substrate is developed to obtain the photoresist pattern. A 5% NaOH solution is used as the developer, and the development time is 30 seconds. 6. Hot Reflow Process: The hot reflow process involves treating a cylindrical structure at high temperature, bringing it to a semi-molten state. Due to surface tension, the cylindrical microstructure gradually diffuses into a hemispherical structure. This process also improves the surface roughness of the microstructure, achieving optical-grade performance. This method requires precise temperature and time control. In this experiment, the reflow temperature was 150 ℃ and the time was 3 min. 7. Electroforming master copy: Before electroplating, a 100 nm thick layer of nickel is deposited on the substrate as a seed layer for electroplating. Then, the photoresist template is immersed in a salt solution containing nickel metal for electroplating. After electroplating, the template is demolded to prepare the nickel template. 8. Spin-coating embossing adhesive: A layer of UV imprint photoresist (Huahai Chengke 3604-09) was spin-coated onto a quartz glass substrate using a spin coater. Spin-coating steps: The imprint photoresist was dropped onto the glass surface and rotated at a low speed of 300 r / min for 5 seconds, then at a high speed of 1000 r / min for 15 seconds. 9. Lamination and exposure: The template is pressed onto a glass substrate coated with photoresist and placed inside a UV nanoimprinter. Heating and pressurizing are applied to completely fill the voids in the nickel nanoimprint template with the imprinting resin. Then, the imprinting resin is cured by UV exposure at an energy of 20 mJ / cm² for 10 min. 10. Demolding: Finally, the embossing template and embossing adhesive are separated to obtain the embossed structure. The light-trapping structure prepared in this embodiment is a hemispherical structure with a period of 12 μm, a base diameter of 10 μm, and a height of 5 μm. Its morphological characteristics are shown in the attached figure. Figure 4 As shown.

[0038] Example 5 Using the template prepared in Example 4, a secondary imprinting technique using ultraviolet nanoimprinting can be performed to obtain a light-trapping structure opposite to the template. The secondary light-trapping structure is a hemispherical pit structure with a period of 12 μm, a base diameter of 10 μm, and a height of 5 μm. Its morphological characteristics are shown in the attached figure. Figure 5 As shown.

[0039] The above content is only a specific implementation example of the present invention, but the scope of protection is not limited to the listed examples, and any approximate substitution is covered within the scope of protection of the present invention.

Claims

1. A low-cost micro / nano imprinted light-trapping glass for photovoltaic cells, characterized in that: The light-trapping structure on the surface of the solar cell glass can be precisely and controllably fabricated in various ways using a combination of UV-LIGA and ultraviolet nanoimprinting techniques. This structured glass has good periodicity and symmetry, which can significantly improve the transmittance of incident light, allowing more photons to enter the cell and thus improving the photoelectric conversion efficiency of the solar cell.

2. The low-cost micro / nano imprinted light-trapping glass for photovoltaic cells according to claim 1, characterized in that: The light-trapping structure can be a cylinder, cone, hemisphere, hemispherical pit, frustum, or other patterns.

3. The low-cost micro / nano imprinted light-trapping glass for photovoltaic cells according to claim 2, characterized in that: The light-trapping structure parameters are as follows: the diameter of the bottom edge of the structure can be between 2um and 20um, the height can be between 1um and 10um, and the period can be between 2um and 20um, including various array arrangements.

4. A low-cost micro / nano imprinted light-trapping glass for photovoltaic cells according to claim 1 or 2, characterized in that: The preparation method includes the following steps: S1. Imprint template prepared using UV-LIGA: (a) Substrate cleaning: Select a suitable substrate for standard semiconductor cleaning process; (b) Spin-coating photoresist: Select the photoresist according to the height of the light-trapping structure for spin-coating; (c) Fabrication of the photomask: Fabricate the photomask according to the bottom diameter and period of the light trapping structure; (d) Pattern transfer: The pattern on the photomask is transferred to the photoresist through exposure and development; (e) Thermal reflow process: Thermal reflow can keep the structure in the photoresist in a semi-molten state, and structures such as cones, frustums and hemispheres can be prepared by diffusion through surface tension; (f) Template preparation: A nickel template was prepared using an electroforming process; S2. Using ultraviolet nanoimprinting technology to imprint the template onto the surface of solar cells or glass: (a) Spin-coating of photoresist: Select a suitable photoresist and spin-coat it onto the surface of the solar cell or glass; (b) Pattern transfer: The template structure is transferred once or twice through molding and exposure; (c) Demolding: Separate the embossing template and the embossing adhesive to obtain the embossed structure.

5. A low-cost micro / nano imprinted light-trapping glass for photovoltaic cells according to claim 4, characterized in that: The thickness of the photoresist and imprinting adhesive is between 1µm and 10µm.

6. A low-cost micro / nano imprinted light-trapping glass for photovoltaic cells according to claims 1-4, characterized in that: The light-trapping structure has a significant anti-reflection effect.

7. A low-cost micro / nano imprinted light-trapping glass for photovoltaic cells according to claims 1-4, characterized in that: The solar cell based on the light-trapping structure can fully absorb incident light, thereby improving the photoelectric conversion efficiency of the device.

8. A low-cost micro / nano imprinted light-trapping glass for photovoltaic cells according to claims 1-4, characterized in that: The light-trapping structure has self-cleaning capabilities, which can significantly improve the sustainability and photoelectric performance of solar cells.